URGENCY OF EARLY CHILDREN EDUCATION IN THE PERSPECTIVE OF HADITS IN CORONAVIRUS PANDEMIC TIME - Afifah Fatihakun Ni'mah Wahidah; Muhammad Alfatih Suryadilaga (Sunan Kalijaga International Journal on Islamic Educational Research, 2020)
Abstract: This article describes the review of several hadiths of the obligations of parents in educating children, which are associated with conditions in the Coronavirus pandemic era. We all know families are the first and major education places for someone, and parents as the key. It has become an obligation for both parents to educate their children, but now there are many parents who forget their obligations to provide education to their children. Education in the family mainly plays a role in developing character, personality, cultural values, religious and moral values, and simple skills. With this current condition where Indonesia is experiencing a coronavirus pandemic, the spread of a very rapid virus makes the government provide policies to its citizens for Physical distances. One of the impacts of this coronavirus pandemic is the field of education, namely learning must be done online (in the network). Furthermore, the role of parents in the Coronavirus pandemic era in child learning. In addition, explaining what factors make learning done at home in the era of the Coronavirus Pandemi and how to transform (change) learning in the context of subsequent learning in the virtual world / social media.